MATLAB Model For Simulation Of Powertrain Customer Collective - Rodrigues, Glen (My University, 2020)
With the increasing impact on global climate change and the contribution of combustion vehicle emissions to this problem, it is time to look for alternative transmission technologies that promote the use of cleaner propulsion systems using electric motors or reduced usage of combustion engines with the help of hybrid transmission. This thesis is mainly aimed at studying the operation of transmission systems involving both electric motor and combustion engine, analyse typical customer cycles and obtain dimensioning data required for transmission design. A systematic approach for determining the duty values of an automotive transmission, for a defined vehicle and driver profile helps a long way in analysing the durability of the said transmission system. The study aims at developing a MATLAB tool to accept inputs in the form of velocity profiles, driver usage profile and a well defined vehicle case to determine the duty cycles of the transmission components. This duty cycle gives an overview of the damage taken by the components in the form of torque and rotational speeds. The data generated may also be used as a dimensioning factor for the components such as gears, differential and driveshafts. The tool primarily focuses on Hybrid Electric Vehicles(HEV) and Battery Electric Vehicles(BEV), with the flexibility of analysing a pure combustion based transmission system. Primary focus of these models is obtaining duty cycles of transmission components like the gearbox, differential and driveshaft. The tool can also be used to study the effects of various damage mechanisms, gear shifting patterns, combustion engine - electric motor sizing, and the effects of inertia on the duty values of transmission components.
Keywords: Transmission; Design; Dimensioning; Customer Cycles; Duty Values; HEV; BEV; Damage Values; Inertia